Digitalisasi Akuntansi dan Pengelolaan Keuangan Usaha Kecil Menengah (UKM) - Karin Chlarista Putri; Siti Khairani (Universitas Multi Data Palembang, 2026)
This study aims to analyze the effect of accounting digitalization on the financial management of Small and Medium Enterprises (SMEs), with financial literacy as a moderating variable in Palembang City. The study employs a quantitative approach with a correlational research design. Data were collected through questionnaires distributed to 121 SME owners located in Sukarami, Ilir Timur I, and Ilir Timur II districts. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The results indicate that accounting digitalization has a positive and significant effect on SME financial management. In addition, financial literacy also has a positive and significant effect on SME financial management. The moderation analysis shows that financial literacy moderates the relationship between accounting digitalization and financial management with a weakening effect. This finding suggests that at higher levels of financial literacy, SMEs tend to be less dependent on accounting digitalization. This study emphasizes the importance of balancing the implementation of accounting technology with the enhancement of financial literacy among SME owners.